If b>1 , the function is increasing and is an exponential growth function.

If 0

**Because b= 2 > 1, then the function represents an exponential growth. The exponential growth function is given by:**

\(A(t)=a(1+r)^t\)

where a is the initial amount, (1+r) is the growth factor, and r is the rate of growth.

Using the value of b,

\(b=1+r \rightarrow 2=1+1\)

Hence, the base in terms of the rate of decay is:

\(y=450(1+1)^x\)

and r is the rate of growth:

\(r=1 \text{ or } 100\%\)

This means that the function increases by 100% as x increases by 1.

\(A(t)=a(1+r)^t\)

where a is the initial amount, (1+r) is the growth factor, and r is the rate of growth.

Using the value of b,

\(b=1+r \rightarrow 2=1+1\)

Hence, the base in terms of the rate of decay is:

\(y=450(1+1)^x\)

and r is the rate of growth:

\(r=1 \text{ or } 100\%\)

This means that the function increases by 100% as x increases by 1.